IDENTIFIKASI SUMBER RISIKO PRODUKSI BROKOLI DI GAPOKTAN LEMBANG AGRI, DESA CIKIDANG, KECAMATAN LEMBANG, KABUPATEN BANDUNG BARAT - Ade Ramnah; Nur Syamsiah; Agriani Hermita Sadeli; Lucyana Trimo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The horticulture sub-sector is an agricultural sub-sector that has an important role in the growth of Gross Domestic Product (GDP) and has enormous potential to be developed in Indonesia. Broccoli is one of the vegetables that has very rapid productivity due to increasing market demand. Gapoktan Lembang Agri is an association of farmer groups that cultivate broccoli vegetables in every activity. however, the productivity of broccoli in Lembang Agri's Gapoktan has fluctuated which hinders the Gapoktan from meeting market demand. The purpose of this study was to identify sources of risk for broccoli production in Gapoktan Lembang Agri. Data analysis in this study used descriptive-qualitative method. The results of the study identified the causes of risk sources for broccoli production in Gapoktan Lembang Agri as many as 22 risk sources.